Mass alphabetization in Sicily after the Unit. Testimonies from the Archive of State of Catania (1861-66) - Denaro, Giusy (Rivista di Storia dell’Educazione, 2020)
This work, part of a broader project on “Literacy and Development in Southern Italy from Italian Unification to the Giolittian Era (1861-1914)”, analyzes, through the sources of the State Archives of Catania, the connection between the processes of modernization and literacy in the South, during the first years after the extension of the Casati Law, looking at the modalities, effectiveness and effective fulfillment of schools institution, by the Catania hinterland Municipalities, as a primary element of economic and social progression of the territory. At the same time, particular attention is given to the role of local ecclesiastical institutions in primary education.